2014
DOI: 10.1084/jem.20131397
|View full text |Cite
|
Sign up to set email alerts
|

Classical Flt3L-dependent dendritic cells control immunity to protein vaccine

Abstract: Protective immunity to protein vaccines is controlled by Flt3L-dependent classical LN-resident dendritic cells, and dampened by migratory dendritic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 71 publications
1
87
0
Order By: Relevance
“…Homeostasis of DCs is therefore paramount for induction of effective immunity to microbes as well as maintenance of immune tolerance to selfantigens. For example, removal of DCs abrogates the initiation of immune responses to exogenous antigens (1,2). Conversely, perturbation of the DC compartment by prolonging DC survival in the mouse leads to autoimmunity (3,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Homeostasis of DCs is therefore paramount for induction of effective immunity to microbes as well as maintenance of immune tolerance to selfantigens. For example, removal of DCs abrogates the initiation of immune responses to exogenous antigens (1,2). Conversely, perturbation of the DC compartment by prolonging DC survival in the mouse leads to autoimmunity (3,4).…”
mentioning
confidence: 99%
“…Conversely, pDCs express TLR-7 and abundant type 1 interferons but lack the ability to present antigen in noninflammatory conditions (7,8). pDCs have been implicated in the pathogenesis of systemic lupus erythematosus (9,10), whereas cDCs are critical for activating killer T cells (CTLs) against Listeria and Plasmodia (1) and immune responses to proteinaceous vaccines (2). The DC subsets have different lifespans (11,12).…”
mentioning
confidence: 99%
“…45 We and others have observed that skin DCs (in the steady state) are transcriptionally far more closely related to each other than to their LN resident counterparts. 28,46,47 This finding was initially surprising, as some skin and LN populations share both common precursors, as well as a capacity for functionally similar properties, such as cross-presentation. Furthermore, even LCs are more closely related to the other skin DC populations, 28 despite arising from a unique developmental pathway, more akin to monocytes and microglia than the remaining skin resident DCs.…”
Section: Abstract: Dendritic Cells DC Targeted Vaccines Immune Tolementioning
confidence: 99%
“…Furthermore, even LCs are more closely related to the other skin DC populations, 28 despite arising from a unique developmental pathway, more akin to monocytes and microglia than the remaining skin resident DCs. 48,49 Moreover, skin DC in the steady-state and during Flt3L treatment maintain a transcriptional signature that is both mature as well as tolerogenic, 28,46 while lymphoid resident DC tend to selectively express these markers during maturation, highlighting broad programming differences between these 2 groups.…”
Section: Abstract: Dendritic Cells DC Targeted Vaccines Immune Tolementioning
confidence: 99%
See 1 more Smart Citation